1980
DOI: 10.1515/zna-1980-1110
|View full text |Cite
|
Sign up to set email alerts
|

Internal Cation Mobilities in the Molten Systems (Li-Na)NO3 and (Na-Cs)NO3

Abstract: For the molten salt systems (Li-Na)N03 and (Na-Cs)N03, relative differences of intei'nal mobilities have been measured with the Klemm method. The internal mobilities, b, are calculated from these data and the available conductivity data. In the mixtures of the former system, &xa is always greater thanIn the latter system, the Chemla crossing point occurs. It is found that bu and &xa in the binary alkali nitrate systems so far investigated are well expressed, except at small molar volumes, by b = {^4/(F-F 0 )} … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…This value would depend on pair potentials implicitly including the concept of ionic size, moveability of coions, and temperature; this would be different from that for the self-diffusion. The existence of such an optimal volume has been suggested also for the internal mobilities from the experimental results of molten alkali nitrate mixtures [3]. For pure KCl in the present case, where the sizes of both ions are rather large, in other words, the attraction between cation and anion is not so strong, the optimal molar volume is expected to be larger than that at normal density, and hence the SEV decreases at higher density.…”
Section: If There Is An Approximately Linear Relation Between Them Isupporting
confidence: 57%
See 1 more Smart Citation
“…This value would depend on pair potentials implicitly including the concept of ionic size, moveability of coions, and temperature; this would be different from that for the self-diffusion. The existence of such an optimal volume has been suggested also for the internal mobilities from the experimental results of molten alkali nitrate mixtures [3]. For pure KCl in the present case, where the sizes of both ions are rather large, in other words, the attraction between cation and anion is not so strong, the optimal molar volume is expected to be larger than that at normal density, and hence the SEV decreases at higher density.…”
Section: If There Is An Approximately Linear Relation Between Them Isupporting
confidence: 57%
“…On the basis of the results of molecular dynamics simulation [1] as well as of experiments [2,3], we have assumed that in transport phenomena of ionic melts such as diffusion and electric conduction, interactions between cation and anion and the relative volume of free space compared with the ionic size are the dominant factors. One way for elucidating the effect of the free-space on transport phenomena is to measure the properties under high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The profiles of the isotherms for (Li, Na)Cl are similar to those of (Li, Na)N0 3 [6] in that the larger cation is more mobile than the smaller one in the whole concentration and temperature range. The sharp increase in b u and b Na with increasing concentration of LiCl is due to the sharp increase in the number density of the Cl~ ions.…”
Section: Discussionmentioning
confidence: 52%
“…Especially (Na, K)N0 3 shows the Chemla effect [5]. In (Li, Na)N0 3 the mobility of Na + is throughout larger than that of Li + [6].…”
Section: Introductionmentioning
confidence: 96%
“…In all these systems, in a certain range of concentration and temperature the Chemla effect was observed, i. e., the mobility of the larger cation is greater than that of the smaller one. Further, we have found that, when Coulombic interaction between the cations and anions is the predominant factor influencing the cationic mobilities, the internal mobilities b are well expressed by [3,4]:…”
Section: Introductionmentioning
confidence: 94%